GAY SELF-PRESENTATION IN SOCIAL INTERACTION (A DRAMATURGICAL STUDY OF THE GAY COMMUNITY IN PALEMBANG CITY) - Diah Ayu Nabilah Karimah; Rizki Hidayat; Adelia Octaviani; Ina Novita Sari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The increasing of gay in Indonesia, including palembang, does not make their existence recognized and accepted in society. Society considers that gay groups do not conform to existing religious and customary norms. This study uses the Dramaturgy theory of Erving Goffman, which suggests that human life is like a theater, which has a front stage and a back stage. This study aims to determine the self-presentation of gay people in Palembang City on the front stage and back stage. The research method used is a qualitative research method by conducting observations and in-depth interviews. The results of this study indicate that there are differences in the self-presentation of gay people on the front stage and back stage. On the front stage, gay people camouflage and hide their true identity. On the backstage, they are themselves, without hiding the identity that they are gay.